IMPLEMENTASI PELESTARIAN BUDAYA P5 DI SD NEGERI KALIASIN 1 SURABAYA STUDI KASUS: PROGRAM KKN - SUKHUFATUL KHUMAIDAH; Nimas Fadhilatur Rohmah; Hanung Sekar Larasati Enggaringtyas; Fatih Anang Arisyadi; Andi Nasution Nasution; Diana Aqidatun Nisa (ARDVIS, 2025)
The Community Service Program (KKN) is an initiative that allows university students to apply their knowledge and skills to help solve problems and develop potential within local communities, while also fostering empathy, responsibility, and independence. The KKN activity conducted by the Visual Communication Design (DKV) Department of UPN Veteran East Java in collaboration with SDN Kaliasin 1 Surabaya implemented the Pancasila Student Profile Strengthening Project (P5). This project aimed to integrate Pancasila values into the learning process through murals, an interactive height measurement tool, and educational posters. Using a participatory approach involving planning, implementation, and evaluation, the project successfully enhanced students’ understanding of Pancasila values, while encouraging creativity and active participation in a fun and character-building learning environment.